The Impact of Legislative Development on the Constitutionality of the Rules of Attribution in Private International Law (A Comparative Study) - Abdul Amir Madhloum, Raghad; Younis Mukhaybar Ghalis , Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The rules of laws conflict are still the usual technical means for solving the problem of international conflict of laws, that its mission is pointing to the specialized law of the legal relationship tainted by a foreign element, but the development of life, especially after the radical transformations that occurred in Iraq in 2003. And openness in all aspects, especially economic, financial, and commercial transactions, these rules have become invalid for application to disputes with an international dimension for two reasons: The first has not changed in spite of the important developments that have taken place internationally since the second half of the last century and because it has not been devoted to the constitutional and economic principles that came out of the 2005 Iraqi constitution. The second: Because Iraq needs investment projects that can contribute to the reconstruction of its infrastructure and the reconstruction of the country. The judges need rules that would assist and guide the judge in choosing the law to be applied in the disputes before the court, and in light of this development, it is obligatory for the Iraqi legislator to review the rules of attribution in response to new developments.